Binderless NiCo2O4@NiMoO4 core-shell nanosheet array material and preparation method thereof - YIN HUAN; ZHAO RUI; TANG HONGYANG; XUE WEIDONG (2018)
The invention belongs to the field of electrode material synthesis, and provides a binderless NiCo2O4@NiMoO4 core-shell nanosheet array material and a preparation method thereof. The binderless NiCo2O4@NiMoO4 core-shell nanosheet array material comprises Ni foam, NiCo2O4 nanosheets growing on the surface of the Ni foam and NiMoO4 nanosheets growing on the surface of the NiCo2O4 nanosheets, and theNiMoO4 nanosheets and the NiCo2O4 nanosheets form a core-shell structure. The material has a core-shell nanosheet array structure with the morphology to be stacked honeycomb nanosheets, a composite material is directly used as an electrode material of a super capacitor, high specific capacitance and cycle stability are realized, the specific capacitance of the NiCo2O4@NiMoO4 core-shell nanosheetarray material is 6.91 F cm<-2>, and when the current density is 5 mA cm<-2> and after 5000 times of charge and discharge cycles happen, the capacitance retention ratio is 76%. Besides, the material is high in purity, good in